Thinking Aloud as an Effective Strategy in Foreign Language Learning: Philosophical Analysis, Methods, and Practical Implementation - Khalid Addamegh; Sara Al Qahtani (Indonesian Journal of Arabic Studies, 2024)
Purpose – This study aims to explore the philosophy, methodology, and practical implementation of the Thinking Aloud strategy in second language (L2) and foreign language learning. Thinking Aloud is a cognitive-based learning strategy that enables learners to verbalize their thought processes, thereby enhancing reflective understanding and active communication skills. Design/methods/approach – This research employs a qualitative approach with a descriptive-analytical design, supported by literature studies from various primary and secondary sources, including Scopus and Springer-indexed journals. Data were analyzed using content analysis based on educational theories, cognitive psychology, and second language studies. Findings – The findings reveal that the Thinking Aloud strategy not only strengthens learners' understanding of the target language but also provides practical insights for educators to identify students' learning challenges. Additionally, this study highlights the potential adaptation of this strategy for cross-cultural learning contexts, which has been underexplored in the literature. Research implications – The primary contributions of this research include the development of a comprehensive guide for Thinking Aloud implementation, the integration of theory and practice, and a holistic approach encompassing philosophical, practical, and critical aspects. Therefore, this study establishes a robust foundation for innovating more reflective and effective language learning methods in the globalization era.الملخصتهدف هذه الدراسة إلى استكشاف فلسفة ومنهجية وتنفيذ استراتيجية "التفكير بصوت عالٍ" في تعلم اللغة الثانية (L2) واللغات الأجنبية. "التفكير بصوت عالٍ" هي استراتيجية تعلم تعتمد على الإدراك تمكن المتعلمين من التعبير اللفظي عن عمليات تفكيرهم، مما يعزز الفهم التأملي ومهارات الاتصال النشطة. تستخدم هذه الدراسة منهجًا نوعيًا بتصميم وصفي تحليلي، مدعومًا بدراسات أدبية من مصادر أولية وثانوية متنوعة، بما في ذلك المجلات المفهرسة في سكوبس وسبروينجر. تم تحليل البيانات باستخدام تحليل المحتوى استنادًا إلى نظريات التعليم وعلم النفس الإدراكي ودراسات اللغة الثانية. تكشف النتائج أن استراتيجية "التفكير بصوت عالٍ" لا تعزز فقط فهم المتعلمين للغة المستهدفة، بل توفر أيضًا رؤى عملية للمعلمين لتحديد تحديات تعلم الطلاب. بالإضافة إلى ذلك، تبرز هذه الدراسة إمكانية تكييف هذه الاستراتيجية لسياقات التعلم عبر الثقافات، والتي لم يتم استكشافها بشكل كافٍ في الأدبيات. تشمل المساهمات الرئيسية لهذه الدراسة تطوير دليل شامل لتنفيذ "التفكير بصوت عالٍ"، وتكامل النظرية مع الممارسة، ونهجًا شاملاً يغطي الجوانب الفلسفية والعملية والنقدية. وبالتالي، تؤسس هذه الدراسة قاعدة قوية لابتكار طرق تعلم لغوية أكثر تأملاً وفعالية في عصر العولمة.